Postcomposition. (Southern Illinois University Press, 2011)
Leading a burgeoning self-critical moment in composition studies and writing program administration, Postcomposition is a fundamental reconsideration of the field that attempts to shift the focus away from pedagogy and writing subjects and toward writing itself. In this forceful and reasoned critique of many of the primary tenets and widely accepted institutional structures of composition studies, Sidney I. Dobrin delivers a series of shocks to the system meant to disrupt the pedagogical imperative and move beyond the existing limits of the discipline. Dobrin evaluates the current.